Teatralitat i poesia en Vicent Andrés Estellés: variacions escèniques sobre l'espill - Xavier Vellón Lahoz (Caplletra: Revista Internacional de Filologia, 2014)
The article analyses several reading and dramatisation performances of Estellés’ texts, taking into account the dialogue as an ideological construction and the scenographical dimension as an explanation or reinforcement of the author’s unchanging poetics: the reflections about the identity, the body and the objects.